234k views
0 votes
Please answer quickly 2x^2-x-6= (2x+ ) (x- )

User Sho
by
4.9k points

1 Answer

5 votes

Answer: I hope this is the correct answer for you.

Step-by-step explanation:

2x^2 + x - 6 = 2x^2 + 4x - 3x - 6

= 2x(x + 2) - 3(x + 2) = (x +2)(2x - 3) (Ans)

Or by completing the square method,

2x^2 + x - 6 = 2[x^2 + (1/2)x] - 6

=2[x^2 + (1/2)x + (1/4)^2 - (1/4)^2] - 6

=2[(x+1/4)^2 - 1/16] - 6

=2(x + 1/4)^2 - 1/8 - 6

=2(x + 1/4)^2 - 49/8

=2[(x + 1/4)^2 - 49/16]

=2[(x + 1/4)^2 - (7/4)^2]

=2[x + 1/4 + 7/4][x + 1/4 -7/4]

=2(x + 2)(x - 3/2)

=(x + 2)(2x - 3) (Ans)

f(x) = a x2 + b x + c

then

f(x) = a (x - x1) (x - x2)

For your problem we have the roots given by

\displaystyle \frac{-1 \pm \sqrt{1^2 - 4 (2) (-6)}}{2 (2)}= \frac{-1 \pm \sqrt{49}}{4} = \frac{-1 \pm 7}{4}

2(2)

−1±

1

2

−4(2)(−6)

=

4

−1±

49

=

4

−1±7

which gives -2 and 3/2 as the roots

So

f(x) = 2x2 + x - 6 = 2 (x + 2) (x - 3/2) = (x + 2) (2 x - 3)

Which, thankfully, is the same thing given above.

User Leze
by
5.1k points